The descent. Part 2 [videorecording (DVD)] - Harris, Jon, 1967-; Colson, Christian; MacKinnon, Ivana; McCarthy, James; Blakeson, J.; Watkins, James, 1978-; Macdonald, Shauna, 1981-; Mendoza, Natalie; Hodge, Douglas; Julyan, David (Lions Gate Films, 2010)
Dazed, bloodied and speechless with trauma, Sarah Carter emerges alone from the Appalachian cave system where the events of the first film took place. Local sheriff Redmond Vaines forces her back underground to help the rescue team which is desperately searching for her five missing girlfriends. Only Sarah knows the terror which lurks in the shadows of the caves. They are about to encounter a new tribe of crawlers, inbred, deformed and even more viciously feral than before.